PERLINDUNGAN HUKUM TERHADAP PESERTA BPJS DALAM PELAYANAN KESEHATAN (Commerce Law, 2021)
This research aims to find out legal protection forms for BPJS members in health services as well as inhibitor factors of the legal protection. Applied research method is normative legal research method using field data as complement. Research report indicates that the implementation of health services toward BPJS members has been conducted in accordance to existing law. However, according to the members, there are certain services that still not implemented maximally. Inhibitor factors of that prevent patients from receiving legal protection are namely the incomplete paper work provided by patients, lack of public socialization on service procedures and required documents as well as numbers of unpaid bills by BPJS members leads to the rejection of services fulfillment.